Analisis Strategi Islandia Mempromosikan Destinasi Pariwisata Melalui Industri Film Tahun 2020 - 2023 - Salsabilah, Ayni (2023)
Iceland is a country that gets the nickname "Land of Fire and Ice" because of its unique geography of contiguous volcanoes and ice glaciers. That is one of Iceland's charms in attracting tourists. Sector Iceland's tourism has contributed the largest revenue to the economy of Iceland since the financial crisis in 2008. Because of that, during the COVID-19 pandemic to close the movement, the Icelandic government made various efforts to revive tourism halted due to COVID-19, one of them through the development of the film industry. This research aims to describe how the strategy used by Iceland to get promoting tourism destinations through the film industry in 2020 – 2023. This research uses descriptive research methods through models capitalizing on film marketing opportunities from Hudson & Ritchie. Results of research This is the government of Iceland has devised a strategy through policy releases movies for the first time. These strategies can be grouped into five factors: Destination Marketing Activities, Destination Attributes, Specific Factors , Films, Government Efforts & Film Commissions, and Locations.